New Insights in the Management of Antipsychotics in the Treatment of Schizophrenia in a Patient with Prolactinoma: A Case Report and Review of the Literature - Elvis Henrique Santos Andrade; Pedro Mario Pan; Paula F. Ramalho da Silva; Ary Gadelha (Case Reports in Medicine)
Prolactinomas are the commonest pituitary adenomas and the major pathological cause of hyperprolactinaemia. Symptomatic prolactinomas are treated mainly by dopamine agonists; surgery and radiotherapy are options for nonresponders. Schizophrenia treatment is based on antipsychotics, which acts mainly at serotonergic and dopaminergic systems. We report a case of a 39-year-old schizophrenic male patient that was diagnosed with a macroprolactinoma 8 years after his first psychotic episode. The association of Schizophrenia and prolactinoma represents a clinical challenge once the treatment of one disease can exacerbate the symptoms of the other.